Subtropical fruits making farmers prosperous - Rajan, Shailendra; Singh, V K (Indian Horticulture, 2019)
The subtropical fruits — mango, guava etc. have been substantially contributing towards food, nutritional security and livelihood to a vast majority of farming community for a long time. About 40% of the total fruit production is contributed by subtropical fruits. Though, it is a major contributor towards total fruit production, farmers’ income is low because of low average yield compared to other parts of the world. Presently, a variety of opportunities by mitigating diverse challenges and constraints addressed through scientific innovations and technologies. Adoption of technologies like high-yielding and regularbearing varieties with better fruit quality, plant density optimization, canopy architecture manipulation, rejuvenation of old and senile orchards, effective management of diseases and pest, post-harvest interventions required for reducing losses, value-addition and marketing network are major interventions which can improve the mango and guava farmers’ income, improving economy and livelihood of a large number of fruit growers.